Global scientific trends in laparoscopy and gastric cancer in the 21st century: A bibliometric and visual mapping analysis - Han, Hongmin; Wang, Zhanwei; Zhao, Xiaodan; Li, Guosheng; Fu, Yuan; Wang, Zhongqing; Wang, Hongyan (Frontiers in Oncology, 2023)
Abstract Aims: To use visual mapping and bibliometrics to analyze and summarize the valuable information on laparoscopic surgery for gastric cancer (GC) obtained in the last 20 years, so as to determine the research hotspots and trends in this field. Methods: We screened all literature on laparoscopic surgery for GC in the Web of Science published from 2000 to 2022 and analyzed the research hotspots and trends in this field using VOSviewer. Results: A total of 2796 reports from 61 countries and regions were selected. Japanese researchers published the most papers (n=946), followed by those from China (n=747) and South Korea (n=557). Papers from Japan also had the most citations (n=21,836). Surgical Endoscopy and Other Interventional Techniques published the most reports on laparoscopic surgery for GC (n=386) and also had the highest total number of citations (n=11,076), making this journal the most authoritative in this field. Among the institutions, researchers from Seoul National University in South Korea had the highest numbers of published papers and citations. The keywords of the articles could be divided into five categories: surgical methods for GC, short-term and long-term efficacy of laparoscopic surgery, guiding role of laparoscopy in the treatment of advanced GC, diagnosis and treatment of early gastric cancer (EGC), and lymph node dissection. Keywords such as “laparoscopic proximal gastrectomy”, “surgical outcomes”, and “esophagogastric junction” have emerged recently, and relevant studies on laparoscopic surgery for adenocarcinoma of esophagogastric junction（AEG）have gradually become a hot topic and trend. Conclusion: This study adopted bibliometric analysis to identify the current research hotspots and research trends in the field of laparoscopic surgery for GC. Five main research hotspots of laparoscopic surgery for GC were also identified. Laparoscopic surgery for AEG may become an important research focus in the future.